Language and Gender Representation in Kate Chopin’s the Story of An Hour - Vivi Novalia Sitinjak; Natalia br. Surbakti; Cindy Margaretta Br Sianturi; Geby Amanda Sihombing (Jurnal Dieksis ID, 2026)
The urgency of this research lies in examining language and gender representation in The Story of an Hour to uncover how Kate Chopin challenges patriarchal ideology and constructs female autonomy through narrative discourse. This study examines how linguistic features construct gender representation in Kate Chopin’s The Story of an Hour. While previous studies have largely focused on feminist themes and ideological interpretations, limited attention has been paid to the linguistic mechanisms through which gender ideology is articulated. Addressing this gap, this study applies feminist linguistics and Critical Discourse Analysis to explore how language reflects women’s emotional experience and social position within a nineteenth-century patriarchal context. Using a qualitative research design, data were collected through documentation of the short story text and analyzed through close reading. Linguistic features such as lexical choices, figurative language, imagery, narrative voice, and discourse structure were examined. The findings reveal that female experience is represented through indirect and emotive language, with freedom portrayed as an internal and temporary realization. Narrative voice confines women’s expression to private consciousness, while authoritative discourse reinforces patriarchal interpretations. Nevertheless, narrative irony enables subtle resistance. Overall, this study concludes that gender ideology in The Story of an Hour is not simply conveyed through thematic content but is fundamentally constructed through linguistic choices, narrative voice, and discourse structures. By foregrounding language as a site of power and resistance, the study highlights the crucial role of linguistic analysis in uncovering how gendered meanings are produced, sustained, and subtly challenged in literary texts.